Performance of futureteachers on verbal "part of" problem - Sanz, Maria T (2021)
This paper presents the preliminary results of a pilot experiment in which prospective elementary school teachers have to solve arithmetic problems from elementary school textbooks related to the use of fractions through a technological environment. The main objective of the experiment, in addition to assessing the knowledge of the future teachers, is to measure the performance of the students based on the type of feedback received after answering multiple choice questions. The data collected allow us to verify the positive impact of using messages with aids compared to using only correct or error messages. On the other hand, we consolidate a methodology to use the measurement of student reading time provided by the technological environment as a proxy to determine the complexity of verbal problems.